The sphere of techno-media consumption and its role in the socialization of a group of preschool children in the city of Medellin: A case study (2022)
ABSTRACT: This paper presents some of the approaches developed in the doctoral thesis entitled Techno-media consumption and children's socialization: A case study with a group of preschool children in Medellin. The study with a qualitative design and based on a case study with a group of preschool children shows the role played by the sphere of techno-media consumption in the socialization process of the children under study. The work starts from the central idea according to which techno-media consumption - the culture of techno-media consumption - acts as a socializing instance and as an orientation system from which and with whose influence children deal with the world. This orientation system offers different kinds (knowledge, themes, values, beliefs, rules, ways of acting, ways of relating to others and themselves, ritualized ways of acting, material elements and artifacts, images, symbols, among others) to children which, once appropriated and internalized (socialization) become interpretative patterns based on which they elaborate, interpret, and act in the world.